An Efficiency Energy And Load Supply Control (Ats) Illumination Of University Pembangunan Pancabudi Based On Solar Power Load Supply - Teja Priyana; Solly Aryza; Adi Sastra Tarigan (Sean Institute, 2021)
Workload analysis is an effort to calculate the workload on the work unit by adding up all the workloads and then dividing by the individual work capacity per unit of time. This study aims to determine the need for health workers (paramedics) by calculating the difference between the ideal number of paramedics (nurses and pharmacists) and the reality (WISN difference) and calculating the workload at Royal Prima University Medan. This type of research is descriptive with quantitative methods. and qualitatively simultaneously to analyze the workload and obtain the number of paramedical staff, namely nursing and pharmacy staff based on the Workload Indicator Staffing Need (WISN) method.